The influence of personality on trajectories of distress, health and functioning in mild-to-moderately depressed adults with type 2 diabetes. Issue 3 (15th March 2020) - Sanatkar, Samineh; Baldwin, Peter; Clarke, Janine; Fletcher, Susan; Gunn, Jane; Wilhelm, Kay; Campbell, Lesley; Zwar, Nick; Harris, Mark; Lapsley, Helen; Hadzi-Pavlovic, Dusan; Christensen, Helen; et al.
ABSTRACT: Identification of mental health risk is important for optimising diabetes care in type 2 diabetes mellitus (T2DM). Personality is linked to diabetes health and may assist detection of individuals with T2DM most at risk of chronic mental health difficulties. This study examined the moderator effect of personality factors on changes in psychological distress and functioning in adults with T2DM and mild-to-moderate depressive symptoms across a 12-month period. Data were obtained from participants in a randomised controlled trial of adults with T2DM. Participants completed measures of depression (Patient Health Questionnaire-9), anxiety (General Anxiety Disorder-7), general functioning (Work and Social Adjustment Scale), diabetes distress (Diabetes Distress Scale), and diabetes self-management (Self-Management Profile for Type 2 Diabetes) at baseline, 3-, 6- and 12-months. Glycaemic control (HbA1c) was measured at baseline, 6- and 12-months. Two hundred trial completers agreed to complete a personality inventory (Big Five Inventory). Low neuroticism was linked with reduced depression, anxiety, functional impairment and diabetes distress over the year. High extraversion was associated with decreased anxiety and functional impairment. High conscientiousness was linked to increased healthy eating. No personality trait moderated HbA1c levels. Personality screening may help identify mental health risk and guide medical carer approach in T2DM patients.